Synthesis of magnetite nanoparticles using electrochemical oxidation - Ye. Ya. Levitin; I. D. Roy; O. S. Kryskiv; T. M. Chan (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The monodisperse magnetite nanoparticles are promising for use in the biomedical industry for targeted drug delivery, cell separation and biochemical products, Magnetic Resonance Imaging, immunological studies, etc.